Single-step primary open-angle glaucoma and complicated cataract surgery using modified technique of stainless steel Glaucoma Filtration Device implantation - J. A. Gusev (Oftalʹmologiâ, 2014)
Purpose: To analyze the efficacy of novel technique of primary open-angle glaucoma (POAG) and complicated cataract surgery that combines phacoemulsification and modified stainless steel Glaucoma Filtration Device implantation.Methods: 100 patients (120 eyes) with POAG and complicated cataract aged 52‑89 years were included in the study. All patients were divided into 3 groups. In group I, phacoemulsification with non-penetrating deep sclerectomy (NPDS) and collagen drainage device implantation by Malygin B. A. was performed. In group II, phacoemulsification with Glaucoma Filtration Device implantation using standard technique was performed. In group III, phacoemulsification with Glaucoma Filtration Device implantation using improved technique was performed.Results: Following phacoemulsification with NPDS, IOP was decreased by 38 % in a month and by 21 % in a year while visual acuity improved 3,8 times in a year. Following phacoemulsification with Glaucoma Filtration Device implantation using standard technique, IOP was decreased by 41 % in a month and by 39 % in a year while visual acuity improved 4,3 times in a year. Following phacoemulsification with Glaucoma Filtration Device implantation using modified technique, IOP was decreased by 43 % in a month and remains stable in a year while visual acuity improved almost 5 times in a year.Conclusion: Phacoemulsification with Glaucoma Filtration Device implantation using modified technique provides adequate IOP reduction and highest possible functional results in early and late post-op period.